Nutrition, Diet and Food Allergy - Mastrorilli, Carla (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue of Nutrients is addressing the topic 'Nutrition, Diet and Food Allergy'. Globally, food allergy affects 1.5% of adults and 5% of children and this prevalence is increasing in recent decades, representing a public health problem. Different mechanisms are involved in food allergic diseases with distinctive clinical characteristics: IgE-mediated and non-IgE-mediated phenotypes will be distinguished in the Issue, considering the early recent literature on the prevalence, age of onset, follow-up recommendations and duration of food allergies. Moreover, the management of these fascinating diseases will be discussed with particular attention on nutritional hazards, risks of allergic reactions to new allergens, problems with missed labelling (precautionary allergen labelling (PAL)). Especially, the dietary restrictions and the re-introduction of allergens lead to a significant burden for affected patients, fear of accidental ingestions and related risk of severe reactions, resulting in a reduced quality of life among patients with food allergies.